Comparative study to evaluate bone loss during osteotomy using standard drill, bone trephine, and alveolar expanders for implant placement - Darpan Bhargava; Shaji Thomas; Ankit Pandey; Ashwini Deshpande; Sunil Kumar Mishra (Wolters Kluwer Medknow Publications, 2018)
Statement of Problem: Various osteotomy modalities seem to have an impact on the primary and secondary stability of the dental implant. The available literature lacks the comparison of various available osteotomy modalities used for the dental implant placement and its effects on the initial surgical bone removal. Purpose: The purpose of this study is to compare and evaluate the osteotomy sites created using standard drill, bone trephine, and alveolar expanders for dental implant surgery. Materials and Methods: The study was done on ten goat hemimandibles. Three osteotomy sites were prepared at the inferior border of the mandible using standard drill, trephine, and alveolar expander in each hemimandibles and the sites were subjected to cone-beam computed tomography (CBCT). The CBCT images obtained were compared for the amount of cortical bone and bone marrow loss at osteotomy sites in different techniques. Results: The mean and standard deviation of loss of cortical bone with standard drills, trephines, and alveolar expanders was 3.62 ± 4.216 × 10−2, 3.6 ± 4.681 × 10−16 and 3.15 ± 7.071 × 10−2. At the middle-third region, the loss of marrow bone was 3.38 ± 7.88 × 10−2, 2.15 ± 8.498 × 10−2 and 0.03 ± 9.487 × 10−2, and at lower third region, it was 2.3 ± 4.714 × 10−2, 0.02 ± 6.325 × 10−2, and 0.0, respectively. Conclusion: CBCT images showed minimum bone loss with the use of alveolar expander which may be due to the lateral bone condensation rather the removal of the marrow. Trephine showed less marrow removal in comparison to the standard drill used for dental implant surgery.